Europäische Diskursgemeinschaft: Projektskizze einer sprachvergleichenden Diskursanalyse - Atayan, Vahram; Felder, Ekkehard; Fetzer, Bettina; Mattfeldt, Anna; Moretti, Daniele; Straube, Annika; Wachter, Daniel (Linguistik online, 2020)
Europe is a unique framework of communication with similar issues discussed in different linguistic and cultural areas. This paper gives a detailed overview of a discourse linguistic project that analyses this multilingual discourse space. We focus on the issue of vaccination since this is a controversial issue in the media of all countries that are of interest for this study (Germany, Italy, France, UK). Methods from discourse, corpus and computer linguistics are used to identify the most relevant linguistic, argumentative, and emotional patterns in discourse. The paper discusses these methods in detail. We then show how these patterns are annotated in our corpora and how the different kinds of annotations can be analysed in correlation.
Gesehen am 31.01.2022